ANALISIS DAN PENGEMBANGAN MANAJEMEN JARINGAN DENGAN MENGGUNAKAN MIKROTIK RB750 PADA PPM AL-HIDAYAH JAMBI - Syaifudin, Asep; Assegaff, Setiawan (Jurnal Manajemen Sistem Informasi, 2020)
The development of computer networks is growing rapidly, especially with the internet. In the world ofeducation most schools already have computers connected to the internet that function for schooladministration and in the learning process. In the Woman Lab. Computers PPM AL-HIDAYAH Jambi thereis no distribution of bandwidth so there are still slow computers, firewalls that have not been maximized andthere are no notifications if the network has problems. By using proxy we can manage bandwidth usage,network firewall in the Woman Lab. PPM AL-HIDAYAH computer and make notifications. The networkmanagement development method that I use is the Network Development Life Cycle (NDLC). Based on theresults of research conducted by the author is able to share bandwidth usage to client computers equally,able to block web video streaming, able to block social media web, and able to provide notifications in theevent of a problem on the network. With the results of research showing that microtics are able to overcomenetwork problems in the woman Lab. Computers is expected by PPM AL-HIDAYAH Jambi to immediatelyimplement this network management in the Woman Lab. Computer